A influência do movimento escola sem partido no debate educacional brasileiro: da suposta neutralidade a defesa do homeschooling (2004-2020) - Paiva, Gabriel de Abreu Gonçalves de (2021)
The educational achievements in Brazil, historically, followed the process of consolidation of the capitalist order, reflecting its changes and contradictions. In recent decades, conservative groups have been working on a daily basis to build consensus around an authoritarian normatization of education. In practice, the agendas and propositions of the School Without Party Movement (SWPM) are disseminated as necessary and fundamental for the organization of the current Brazilian education, in combat against "ideological indoctrination", "ideological manipulation", and "gender ideology". By proposing the organization of a collective will, publicizing its ideological conceptions as common interests of all Brazilians, the SWPM assumes fascist perspectives that result in the denial of democratic advances. Through apparently moral discourses, their actions are part of a series of measures that are articulated to the ultraliberal economic project, attack the rights of the social body's subordinate classes when they fight for the reduction of the State and the end of its social responsibilities, reflect the interests of the dispute for hegemony of the dominant class fractions in the dynamics of class struggle, and aim, through movements of containment and imposition, to halt the processes of democratization of education, secularization of culture, and secularization of the State. In this thesis, which aims at historically analyzing the SWPM, we seek to locate the role played by the private apparatus of hegemony within the liberal-ultraconservative front in Brazil and its relations with other private apparatuses of hegemony. Methodologically, based on data mining of the SWPM website, defined as the "articulating locus" of the Movement, we extracted sources capable of revealing the relations established between SWPM and other private hegemonic apparatuses. We will discuss, through the chapters of the thesis, the development of the SWPM from its origins in 2004 to the present day, highlighting its leadership in the actions of the liberal-ultraconservative front in defense of the existence of "gender ideology," homeschooling, and the militarization of schools.